New Public Management Critical Riview - Lukman Arif (Journal Research of Social Science, Economics, and Management, 2023)
The emergence of various criticisms directed at public sector organizations eventually gave rise to a public sector management reform movement, namely the concept of New Public Management. In the NPM concept, all leaders or managers are encouraged to be able to find new and innovative ways to get maximum results or to privatize government functions. This research is part of a qualitative research using a systematic review approach. Systematic review is a method that uses previous evidence-based evidence through review, evaluation, structured evaluation, classification and categorization. Because the steps and strategies for carrying out a systematic review are well planned and structured, this method is very different from the method used only to convey literature studies. Based on the results of the analysis that has been carried out, several things that have become critics regarding the implementation of NPM are: 1) decentralization can have a negative impact on community participation, especially in social policies. 2) Refers to the application of management techniques from the private sector to the public sector. Many academic commentators such as Pollitt (1990) and Armstrong (1998) argue that most fields of public service and administration have distinct political, ethical, constitutional, and social dimensions, and that these factors make the public sector different from the private sector. 3) National culture influences the implementation of NPM.